Tinjauan Yuridis Strategi Promosi Satu Harga Dalam Transaksi Jual Beli Pada Toko Wd Collection Kota Pagar Alam - Herma Diana; Mastriati Hini Hermala Dewi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Promotion as the main element in marketing, promotion is carried out as an effort to increase sales by holding meetings, demonstrations, placing advertisements, both electronic advertisements and advertisements in the form of banners and specially packaged to attract buyers. The tight competition in the field of buying and selling products has given rise to a one-price promotion strategy, such as the Rp. 35.000,- department store on Jl. Colonel H. Burlian Simpang Manna Kota Pagar Alam. The heat is carried out by placing a large banner on the store and reading all Rp. 35,000, - the banner is installed both inside the store and outside the store with a striking banner color so that it attracts people's attention to enter the store even though there are also products that are sold at a price of more than 35,000 ,- the problem studied in this research is about the promotion strategy of one price 35,000,- and what is the juridical view on the promotion strategy of one price that conducts a convenience store of Rp. 35,000,-. The results of the juridical review research on the one-price promotion strategy tend to have an element of fraud because in fact there are goods that are sold not at a price of Rp. 35,000, - but if it is punched from a juridical one-price sale and purchase according to civil law is valid if fulfilled the provisions of Article 1320 Civil law regarding the validity of the agreement.